A new species of the genus Myolepta Newman (Diptera: Syrphidae), with short description and key to all species of the M. vara subgroup - van Steenis, Jeroen (Zootaxa, 2020)
The genus Myolepta Newman comprises medium-sized black hoverflies, with yellowish orange abdominal markings in some species. The genus can be divided into several subgroups of which the Myolepta vara (Panzer, 1798) subgroup will be defined here and its species revised. One new species, M. angustifacia sp. n., is described from eastern Siberia. A key to the species of this subgroup is given. Short descriptions and extensive illustrations are provided for all species.